2013
DOI: 10.1210/me.2013-1178
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1R Modulation of Acute GH-Induced STAT5 Signaling: Role of Protein Tyrosine Phosphatase Activity

Abstract: GH is a potent anabolic and metabolic factor that binds its cell surface receptor (GHR), activating the GHR-associated tyrosine kinase, Janus kinase 2, which phosphorylates and activates the latent transcription factor, signal transducer and activator of transcription 5 (STAT5). Some GH actions are mediated by the elaboration of IGF-1, which exerts effects by binding and activating the heterotetrameric tyrosine kinase growth factor receptor, IGF-1R. In addition to this GH-GHR-IGF-1-IGF-1R scheme, we have demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 51 publications
4
26
0
1
Order By: Relevance
“…Osteoblasts were isolated from calvaria of newborn Igf1r flox/flox mice and cultured as described previously (31,33,34,42). LNCaP-vec and LNCaP-shIGF-1R cells were previously described and characterized, as were the conditions of cell culture (33).…”
Section: Cells and Cell Culturementioning
confidence: 99%
See 3 more Smart Citations
“…Osteoblasts were isolated from calvaria of newborn Igf1r flox/flox mice and cultured as described previously (31,33,34,42). LNCaP-vec and LNCaP-shIGF-1R cells were previously described and characterized, as were the conditions of cell culture (33).…”
Section: Cells and Cell Culturementioning
confidence: 99%
“…LNCaP-vec and LNCaP-shIGF-1R cells were previously described and characterized, as were the conditions of cell culture (33). ␥2A-JAK2-GHR-Nluc cells were generated by the cotransfection of ␥2A-JAK2 cells (16,43) with pcDNA3.1(ϩ)/zeo-GHRNluc and a hygromycin-encoding plasmid at a weight ratio as 20:1 and followed by hygromycin selection and single-clone amplification, as described (44).…”
Section: Cells and Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Direct cross talk of GH and IGF-1 downstream signaling has also been investigated. A complex of GHR-JAK2-IGF-1R has been described in several cell types (100 -102), and further studies have indicated that IGF-1R perpetuates GH signaling by preventing PTP1b-mediated suppression of Stat5 activation (103). Starvation and malnutrition lead to a state of GH resistance that can be considered an adaptation of fasting (104).…”
Section: Cross Talk With Other Signaling Pathwaysmentioning
confidence: 99%